Heat insulation coating and preparation method thereof

By using modified expanded vermiculite and eloite powder in insulating and insulating coatings, the existing coatings have solved the problems of unstable thermal reflection effect, poor persistence of insulation effect and insufficient fire resistance, and better insulation, fire resistance and weather resistance.

CN119709000AActive Publication Date: 2025-03-28CHINA PAINT MFG CO SHENZHEN
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411913455.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The thermal reflection effect of existing insulating and thermal insulation coatings is greatly affected by environmental factors, the thermal insulation effect is poor durable, and the fire resistance is insufficient.

Method used

Insulating and thermal insulation coatings containing glass microbeads, ceramic fibers, alumina fibers, ammonium polyphosphate, rutile titanium dioxide, modified expanded vermiculite, modified erolitic powder, dimethylsilylated silica, VP-dimethylaminoethyl methacrylate copolymer and nano-aerogel are used to improve the compatibility and dispersion of components through the preparation method of modified expanded vermiculite and erolitic powder, thereby enhancing the thermal insulation, fire resistance and weather resistance of the coating.

Benefits of technology

It significantly improves the thermal insulation effect and fire resistance of the coating, keeps it stable under different environmental conditions, extends the service life of the coating, and has good weather resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206301780000161
    Figure BDA0005206301780000161
Patent Text Reader

Abstract

The invention provides a heat insulation coating and a preparation method thereof, and belongs to the technical field of coatings. The coating provided by the invention contains glass beads, ceramic fibers, alumina fibers, ammonium polyphosphate, rutile type titanium dioxide, modified expanded vermiculite, modified halloysite powder, dimethylsilylated silica, a VP-dimethylaminoethyl methacrylate copolymer, nano aerogel and other components, has a very good thermal insulation effect, improves the fireproof performance, and can be used as a thermal insulation material for a building. The heat-insulating and fire-resistant effects are lasting and stable. The modified expanded vermiculite, the modified halloysite powder, the silica dimethylsilylate and the VP-dimethylaminoethyl methacrylate copolymer are matched for use, so that a very good synergistic effect is achieved, the heat preservation and heat insulation performance of the coating can be greatly improved, heat conduction can be blocked, the heat insulation and heat preservation effect is achieved, meanwhile, the coating further has excellent weather resistance, and the service life of the coating is prolonged. The cable is waterproof, fireproof and corrosion-resistant, and can maintain a good performance state under complex and changeable weather conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a heat insulating coating and a preparation method thereof. Background Art

[0002] As a new type of thermal insulation material, thermal insulation coating has the advantages of convenient construction, low cost, good thermal insulation effect, and reduces energy consumption. Thermal insulation coating has a wide range of uses, mainly including the following aspects: in the construction field, it can be used for exterior wall insulation, roof insulation, etc.; in the industrial field, it can be used for pipeline insulation, storage tank insulation, industrial equipment insulation, etc.; in the transportation field, it can be used in engine compartments and other parts to play a role in heat insulation and noise reduction; in addition, using thermal insulation coating on the water tank and pipes of solar water heaters can reduce heat loss and improve the efficiency of solar water heaters; it can also be used for thermal insulation of military facilities and equipment to improve their performance and reliability in harsh environments.

[0003] With the continuous advancement of science and technology, people's requirements for the performance of thermal insulation materials are getting higher and higher. Thermal insulation coatings must not only have good thermal insulation properties, but also have waterproof, fireproof, corrosion-resistant and other properties. At the same time, in order to adapt to different application scenarios, thermal insulation coatings also need to have good construction performance and durability.

[0004] At present, there are many kinds of thermal insulation coatings on the market, and the quality is uneven. The following problems generally exist:

[0005] 1. The heat reflection effect is greatly affected by environmental factors: The performance of some heat reflection thermal insulation coatings is closely related to the season, light intensity, surface contamination, etc. The effect is better in the summer when the sun is strong, but in the spring and autumn, on cloudy days or at night, the reflection effect will be greatly reduced. In winter, the reflection of solar heat may increase the heat loss of the building, and the overall thermal insulation performance is unstable.

[0006] 2. The durability of the thermal insulation effect needs to be improved: With the increase of usage time, the coating may age, crack, peel off, etc., resulting in a gradual decline in thermal insulation performance. For example, thermal insulation coatings that are exposed outdoors for a long time will be eroded by natural factors such as ultraviolet rays, wind and rain, and their thermal insulation effect will be greatly affected.

[0007] 3. Fire resistance needs to be improved: Frequent building fire accidents have put forward higher requirements for the fire resistance of thermal insulation materials. Some thermal insulation coatings have poor fire resistance and are easy to burn.

[0008] Therefore, it is necessary to develop and improve thermal insulation coatings with better thermal insulation, fire resistance, corrosion resistance, weather resistance, etc. to meet the increasingly stringent usage requirements. Summary of the invention

[0009] Aiming at the problems that the heat reflection effect of existing thermal insulation coatings is greatly affected by environmental factors, the durability of the thermal insulation effect is poor, and the fireproof performance needs to be improved. The present invention provides a thermal insulation coating and a preparation method thereof. The coating contains glass microspheres, ceramic fibers, alumina fibers, ammonium polyphosphate, rutile titanium dioxide, modified expanded vermiculite, modified halloysite powder, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel and other ingredients, and has a good thermal insulation effect, improved fireproof performance, and the thermal insulation and fire-resistant effects are long-lasting and stable. The specific technical scheme is as follows:

[0010] A thermal insulation coating comprises the following raw materials in parts by mass: 25 to 35 parts of glass microspheres, 12 to 20 parts of ceramic fibers, 4 to 8 parts of alumina fibers, 4 to 7 parts of ammonium polyphosphate, 3 to 6 parts of rutile titanium dioxide, 5 to 8 parts of modified expanded vermiculite, 5 to 10 parts of modified halloysite powder, 2 to 5 parts of dimethyl silylated silica, 6 to 10 parts of VP-dimethylaminoethyl methacrylate copolymer, 12 to 18 parts of nano aerogel, 20 to 30 parts of silicone resin, 3 to 4 parts of dispersant, 0.5 to 1 part of leveling agent, 1 to 3 parts of defoamer, 1 to 3 parts of fumed silica and 10 to 15 parts of turpentine.

[0011] In the above-mentioned coating, the preparation method of the modified expanded vermiculite comprises the following steps: drying the expanded vermiculite at a temperature of 100°C to 120°C for 2h to 3h, adding the dried expanded vermiculite to the coating modifier according to the ratio of expanded vermiculite to coating modifier = 1: (5-8), stirring at a temperature of 35°C to 45°C for 1h to 2h to obtain coated modified expanded vermiculite, centrifuging, taking the precipitate to dry at 80°C to 90°C, breaking it up, and obtaining modified expanded vermiculite.

[0012] In the preparation method of the modified expanded vermiculite, the particle size range of the expanded vermiculite is 250-325 mesh; the mass ratio of the coating modifier is ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100: (2-5): (1-3).

[0013] In the above-mentioned coating, the preparation method of the modified halloysite powder comprises the following steps: drying the halloysite powder at a temperature of 100°C to 120°C for 2h to 3h, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder: intercalation modifier = 1: (5 to 8), stirring at a temperature of 35°C to 45°C for 3h to 5h to obtain intercalation-modified halloysite powder, centrifuging, taking the precipitate and drying it at 80°C to 90°C, breaking it up, and obtaining modified halloysite powder.

[0014] In the preparation method of the modified halloysite powder, the particle size range of the halloysite powder is 250-325 mesh sieve; the mass ratio of the intercalation modifier is ethanol: pentaerythritol tetracocoate = 100: (3-8).

[0015] In the above coating, the particle size range of the glass microspheres is 10μm to 250μm, and the wall thickness range is 1μm to 2μm; the diameter range of the ceramic fibers is 3μm to 10μm, and the length is 0.1mm to 0.5mm; the diameter range of the alumina fibers is 3μm to 10μm, and the length is 0.1mm to 0.5mm.

[0016] In the above coating, the particle size range of the ammonium polyphosphate is through a 250-325 mesh sieve; the particle size range of the rutile titanium dioxide is through a 250-325 mesh sieve; the particle size range of the dimethyl silylate silica is through a 200-250 mesh sieve; and the particle size range of the nano aerogel is below 100 nm.

[0017] The preparation method of the above-mentioned thermal insulation coating comprises the following steps:

[0018] S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 800r / min-1000r / min, then add dispersant and turpentine in sequence, and stir for 10min-15min; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1200r / min-1500r / min, and stir for 20min-30min; obtain mixture A;

[0019] S2: Transfer the mixture A to a sand mill, add grinding media, and grind at 500 r / min to 800 r / min for 1 h to 2 h to improve the uniformity and flatness of the coating; filter and remove the grinding media to obtain ground material B;

[0020] S3: Transfer the ground material B back to the high-speed disperser, add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a rotation speed of 600r / min to 800r / min, and stir for 15min to 25min; finally, add the leveling agent and defoamer, and continue stirring for 5min to 10min to obtain a uniform and stable thermal insulation coating.

[0021] In S2 of the above preparation method, the grinding media are glass beads with a diameter of 2 mm to 3 mm; the grinding media are added in an amount of 30 to 40 parts by mass.

[0022] In the above preparation method, the glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

[0023] The present invention provides a heat-insulating coating and a preparation method thereof, and the beneficial effects are as follows:

[0024] 1. After modification, the surface of expanded vermiculite is coated with a coating modifier composed of dicetyl stearyl dimer linoleate and PVPK30. This coating modifier can improve the compatibility of expanded vermiculite with other components in the coating, making it more evenly dispersed in the coating system. Unmodified expanded vermiculite itself has certain thermal insulation properties. Due to its better dispersibility, the modified expanded vermiculite can more evenly distribute these air spacing structures in the coating, reducing the channels for heat conduction, thereby further improving the thermal insulation performance of the coating. Unmodified expanded vermiculite itself is an inorganic mineral with good fire resistance. After modification, on the one hand, its own fire resistance is still retained, and on the other hand, better dispersibility enables it to more effectively form a barrier layer in the coating under high temperature environment, preventing flame penetration and enhancing the overall fire resistance of the coating. The components in the coating modifier form a certain protective film on the surface of expanded vermiculite. When encountering corrosive substances, this protective film can first contact with the corrosive substances, slowing down the erosion of the corrosive substances on the expanded vermiculite, thereby improving the corrosion resistance of the expanded vermiculite in the paint and also helping to improve the overall corrosion resistance of the paint. It is also because the protective film formed on the surface of the expanded vermiculite by the coating modifier can resist the influence of climate factors such as ultraviolet rays, moisture and temperature changes. For example, the protective film can reduce the damage of ultraviolet rays to the structure of the expanded vermiculite, so that it can better maintain the structural integrity in a long-term outdoor environment and enhance the weather resistance of the paint.

[0025] 2. Modified halloysite powder is modified by pentaerythritol tetracocoate intercalation. After modification, the surface properties of halloysite powder are improved, the interaction with other components in the coating is enhanced, the dispersibility is improved, and it can be more evenly distributed in the coating system. The low thermal conductivity of unmodified halloysite powder helps to keep warm. After modification, due to its more even dispersion in the coating, the nano-tubular structure of halloysite powder can more effectively absorb air and form a more continuous low heat conduction channel, reduce heat transfer, and improve the thermal insulation performance of the coating. The modified halloysite powder is more evenly distributed in the coating, and when encountering high temperatures of fire, it can better cooperate with other fire-retardant ingredients, such as ammonium polyphosphate, to prevent the spread of flames. At the same time, its own structure can also play a certain role in blocking heat at high temperatures, enhancing the overall fire retardant performance of the coating. The modified structure formed by the intercalation modifier on the surface and inside of the halloysite powder can play a certain isolation role. When the paint comes into contact with corrosive substances, the modified halloysite powder can better resist the invasion of corrosive substances, reduce the damage to its structure caused by corrosion, and thus improve the overall corrosion resistance of the paint. The modified structure of the surface of the modified halloysite powder can effectively resist the influence of environmental factors such as ultraviolet rays, moisture and temperature changes. For example, under ultraviolet radiation, the modified structure can reduce the damage of ultraviolet rays to the internal structure of the halloysite powder, making it more stable in long-term outdoor environments, thereby improving the weather resistance of the paint.

[0026] 3. Adding silica dimethyl silylate can improve the water resistance and weather resistance of the coating. Silica dimethyl silylate forms a hydrophobic siloxane network structure on the surface of the coating, which can prevent the intrusion of moisture and harmful gases, and can resist the influence of climate factors such as ultraviolet rays, thereby improving the weather resistance of the coating.

[0027] 4. Adding VP-dimethylaminoethyl methacrylate copolymer can improve the rheological properties and homogeneity of the coating, making it have better construction performance, and at the same time help improve the adhesion and weather resistance of the coating. The copolymer can form a protective film on the surface of the coating to prevent ultraviolet rays and moisture from damaging the coating and improve the weather resistance of the coating.

[0028] 5. The present invention designs the grinding step parameters according to the characteristics of each component raw material. Grinding improves the uniformity of the coating and improves the particle size, thereby ensuring the thermal insulation, fire resistance, corrosion resistance and weather resistance of the coating to a certain extent.

[0029] 6. The role of other conventional ingredients: Glass beads play a good role in heat insulation. Ceramic fiber has good heat insulation and high temperature resistance, and can enhance the structural strength of the coating. Alumina fiber improves the high temperature resistance and heat insulation performance of the coating. Ammonium polyphosphate is mainly used to improve the fire resistance of the coating. Rutile titanium dioxide improves the hiding power and weather resistance of the coating. Nano aerogel is a highly efficient thermal insulation material that can greatly improve the thermal insulation performance of the coating.

[0030] In summary, the coating of the present invention contains glass microspheres, ceramic fibers, alumina fibers, ammonium polyphosphate, rutile titanium dioxide, modified expanded vermiculite, modified halloysite powder, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel and other ingredients, and has a good thermal insulation effect, improved fireproof performance, and a long-lasting and stable thermal insulation and fireproof effect. The modified expanded vermiculite, modified halloysite powder, dimethyl silylated silica, and VP-dimethylaminoethyl methacrylate copolymer have a good synergistic effect when used in combination, can greatly improve the thermal insulation and heat insulation performance of the coating, can block heat conduction, and play a role in thermal insulation and heat preservation. At the same time, it also has excellent weather resistance, can be waterproof, fireproof, and corrosion-resistant, and maintains a good performance state under complex and changeable climatic conditions. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0032] Example 1

[0033] A thermal insulation coating comprises the following raw materials in parts by mass: 30 parts of glass microbeads, 16 parts of ceramic fibers, 6 parts of alumina fibers, 5 parts of ammonium polyphosphate, 4 parts of rutile titanium dioxide, 6 parts of modified expanded vermiculite, 8 parts of modified halloysite powder, 3 parts of dimethyl silylate silica, 8 parts of VP-dimethylaminoethyl methacrylate copolymer, 15 parts of nano aerogel, 25 parts of silicone resin, 3.5 parts of dispersant, 0.8 parts of leveling agent, 2 parts of defoamer, 2 parts of fumed silica and 12 parts of turpentine.

[0034] The preparation method of the modified expanded vermiculite comprises the following steps: preparing a coating modifier according to the mass ratio of ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100:3:2; passing the expanded vermiculite through a 250-mesh sieve and taking the sieve bottom; drying the sieved expanded vermiculite at 110°C for 2.5h, adding the dried expanded vermiculite to the coating modifier according to the ratio of expanded vermiculite: coating modifier = 1:6, stirring at 40°C for 1.5h to obtain coated modified expanded vermiculite, centrifuging, taking the precipitate and drying it at 85°C, breaking it up, and obtaining the modified expanded vermiculite.

[0035] In the above-mentioned coating, the preparation method of the modified halloysite powder comprises the following steps: preparing an intercalation modifier according to the mass ratio of ethanol: pentaerythritol tetracocoate = 100:5; passing the halloysite powder through a 250-mesh sieve and taking the sieve bottom; drying the sieved halloysite powder at 110°C for 2.5h, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder: intercalation modifier = 1:6.5, stirring at 40°C for 4h to obtain intercalation-modified halloysite powder, centrifuging, taking the precipitate and drying it at 85°C, breaking it up, and obtaining modified halloysite powder.

[0036] In the above coating, the particle size range of ammonium polyphosphate is below 250 mesh sieve; the particle size range of the rutile titanium dioxide is below 250 mesh sieve; the particle size range of the dimethyl silylate silica is below 200 mesh sieve.

[0037] The preparation method of the above-mentioned thermal insulation coating comprises the following steps:

[0038] The glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

[0039] S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 900 r / min, then add dispersant and turpentine in sequence, and stir for 12 minutes; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1300 r / min, and stir for 25 minutes; obtain mixture A.

[0040] S2: Transfer mixture A to a sand mill, add 35 parts by mass of grinding media, i.e. glass beads with a diameter of 2 mm, and grind at 600 r / min for 1.5 h to improve the uniformity and flatness of the coating; filter and remove the grinding media to obtain ground material B.

[0041] S3: Transfer the ground material B back to the high-speed disperser, add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a speed of 700 r / min, and stir for 20 minutes; finally, add the leveling agent and defoamer, and continue stirring for 8 minutes to obtain a uniform and stable thermal insulation coating.

[0042] Example 2

[0043] A thermal insulation coating comprises the following raw materials in parts by mass: 25 parts of glass microbeads, 12 parts of ceramic fibers, 4 parts of alumina fibers, 4 parts of ammonium polyphosphate, 3 parts of rutile titanium dioxide, 5 parts of modified expanded vermiculite, 5 parts of modified halloysite powder, 2 parts of dimethyl silylate silica, 6 parts of VP-dimethylaminoethyl methacrylate copolymer, 12 parts of nano aerogel, 20 parts of silicone resin, 3 parts of dispersant, 0.5 parts of leveling agent, 1 part of defoamer, 1 part of fumed silica and 10 parts of turpentine.

[0044] The preparation method of the modified expanded vermiculite comprises the following steps: preparing a coating modifier according to the mass ratio of ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100:2:1; passing the expanded vermiculite through a 250-mesh sieve and taking the sieve bottom; drying the sieved expanded vermiculite at 100°C for 2h, adding the dried expanded vermiculite to the coating modifier according to the ratio of expanded vermiculite: coating modifier = 1:5, stirring at 35°C for 1h to obtain coated modified expanded vermiculite, centrifuging, taking the precipitate and drying it at 80°C, breaking it up, and obtaining the modified expanded vermiculite.

[0045] In the above-mentioned coating, the preparation method of the modified halloysite powder comprises the following steps: preparing an intercalation modifier according to the mass ratio of ethanol: pentaerythritol tetracocoate = 100:3; passing the halloysite powder through a 250-mesh sieve and taking the sieve bottom; drying the sieved halloysite powder at 100° C. for 2 hours, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder: intercalation modifier = 1:5, stirring at 35° C. for 3 hours to obtain intercalation-modified halloysite powder, centrifugally separating, taking the precipitate and drying it at 80° C., breaking it up, and obtaining modified halloysite powder.

[0046] In the above coating, the particle size range of ammonium polyphosphate is below 250 mesh sieve; the particle size range of the rutile titanium dioxide is below 250 mesh sieve; the particle size range of the dimethyl silylate silica is below 200 mesh sieve.

[0047] The preparation method of the above-mentioned thermal insulation coating comprises the following steps:

[0048] The glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

[0049] S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 800 r / min, then add dispersant and turpentine in sequence, and stir for 10 min; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1200 r / min, and stir for 20 min; obtain mixture A.

[0050] S2: Transfer mixture A to a sand mill, add 30 parts by mass of grinding media, i.e., glass beads with a diameter of 2 mm, and grind at 500 r / min for 1 hour to improve the uniformity and flatness of the coating; filter and remove the grinding media to obtain ground material B.

[0051] S3: Transfer the ground material B back to the high-speed disperser, add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a speed of 600 r / min, and stir for 15 minutes; finally, add the leveling agent and defoamer, and continue stirring for 5 minutes to obtain a uniform and stable thermal insulation coating.

[0052] Example 3

[0053] A thermal insulation coating comprises the following raw materials in parts by mass: 25 parts of glass microbeads, 20 parts of ceramic fibers, 4 parts of alumina fibers, 7 parts of ammonium polyphosphate, 3 parts of rutile titanium dioxide, 8 parts of modified expanded vermiculite, 5 parts of modified halloysite powder, 5 parts of dimethyl silylated silica, 6 parts of VP-dimethylaminoethyl methacrylate copolymer, 18 parts of nano aerogel, 20 parts of silicone resin, 4 parts of dispersant, 0.5 parts of leveling agent, 3 parts of defoamer, 1 part of fumed silica and 13 parts of turpentine.

[0054] The preparation method of the modified expanded vermiculite comprises the following steps: preparing a coating modifier according to the mass ratio of ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100:2:3; passing the expanded vermiculite through a 250-mesh sieve and taking the sieve bottom; drying the sieved expanded vermiculite at 120°C for 2h, adding the dried expanded vermiculite to the coating modifier according to the ratio of expanded vermiculite: coating modifier = 1:8, stirring at 35°C for 2h to obtain coated modified expanded vermiculite, centrifuging, taking the precipitate and drying it at 80°C, breaking it up, and obtaining the modified expanded vermiculite.

[0055] In the above-mentioned coating, the preparation method of the modified halloysite powder comprises the following steps: preparing an intercalation modifier according to the mass ratio of ethanol: pentaerythritol tetracocoate = 100:8; passing the halloysite powder through a 250-mesh sieve and taking the sieve bottom; drying the sieved halloysite powder at 120° C. for 2 hours, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder: intercalation modifier = 1:8, stirring at 35° C. for 5 hours to obtain intercalation-modified halloysite powder, centrifuging, taking the precipitate and drying it at 80° C., breaking it up, and obtaining modified halloysite powder.

[0056] In the above coating, the particle size range of ammonium polyphosphate is below 325 mesh sieve; the particle size range of the rutile titanium dioxide is below 250 mesh sieve; the particle size range of the dimethyl silylate silica is below 250 mesh sieve.

[0057] The preparation method of the above-mentioned thermal insulation coating comprises the following steps:

[0058] The glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

[0059] S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 800 r / min, then add dispersant and turpentine in sequence, and stir for 15 minutes; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1200 r / min, and stir for 30 minutes; obtain mixture A.

[0060] S2: Transfer mixture A to a sand mill, add 30 parts by mass of grinding media, i.e. glass beads with a diameter of 3 mm, and grind at 500 r / min for 2 h to improve the uniformity and flatness of the coating; filter and remove the grinding media to obtain ground material B.

[0061] S3: Transfer the ground material B back to the high-speed disperser, add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a speed of 600 r / min, and stir for 25 minutes; finally, add the leveling agent and defoamer, and continue stirring for 5 minutes to obtain a uniform and stable thermal insulation coating.

[0062] Example 4

[0063] A thermal insulation coating comprises the following raw materials in parts by mass: 35 parts of glass microbeads, 20 parts of ceramic fibers, 8 parts of alumina fibers, 7 parts of ammonium polyphosphate, 6 parts of rutile titanium dioxide, 8 parts of modified expanded vermiculite, 10 parts of modified halloysite powder, 5 parts of dimethyl silylated silica, 10 parts of VP-dimethylaminoethyl methacrylate copolymer, 18 parts of nano aerogel, 30 parts of silicone resin, 4 parts of dispersant, 1 part of leveling agent, 3 parts of defoamer, 3 parts of fumed silica and 15 parts of turpentine.

[0064] The preparation method of the modified expanded vermiculite comprises the following steps: preparing a coating modifier according to the mass ratio of ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100:5:3; passing the expanded vermiculite through a 325-mesh sieve and taking the sieve bottom; drying the sieved expanded vermiculite at 120°C for 3h, adding the dried expanded vermiculite to the coating modifier according to the ratio of expanded vermiculite: coating modifier = 1:8, stirring at 45°C for 2h to obtain coated modified expanded vermiculite, centrifuging, taking the precipitate and drying it at 90°C, breaking it up, and obtaining the modified expanded vermiculite.

[0065] In the above-mentioned coating, the preparation method of the modified halloysite powder comprises the following steps: preparing an intercalation modifier according to the mass ratio of ethanol: pentaerythritol tetracocoate = 100:8; passing the halloysite powder through a 325-mesh sieve and taking the sieve bottom; drying the sieved halloysite powder at 120°C for 3h, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder: intercalation modifier = 1:8, stirring at 45°C for 5h to obtain intercalation-modified halloysite powder, centrifuging, taking the precipitate and drying it at 90°C, breaking it up, and obtaining modified halloysite powder.

[0066] In the above coating, the particle size range of ammonium polyphosphate is below 325 mesh sieve; the particle size range of rutile titanium dioxide is below 325 mesh sieve; the particle size range of dimethyl silylate silica is below 250 mesh sieve.

[0067] The preparation method of the above-mentioned thermal insulation coating comprises the following steps:

[0068] The glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

[0069] S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 1000 r / min, then add dispersant and turpentine in sequence, and stir for 15 minutes; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1500 r / min, and stir for 30 minutes; obtain mixture A.

[0070] S2: Transfer mixture A to a sand mill, add 40 parts by mass of grinding media, i.e. glass beads with a diameter of 3 mm, and grind at 800 r / min for 2 h to improve the uniformity and flatness of the coating; filter and remove the grinding media to obtain ground material B.

[0071] S3: Transfer the ground material B back to the high-speed disperser, and add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a speed of 800 r / min, and stir for 25 minutes; finally, add the leveling agent and defoamer, and continue stirring for 10 minutes to obtain a uniform and stable thermal insulation coating.

[0072] Example 5

[0073] A thermal insulation coating comprises the following raw materials in parts by mass: 35 parts of glass microbeads, 12 parts of ceramic fibers, 8 parts of alumina fibers, 4 parts of ammonium polyphosphate, 6 parts of rutile titanium dioxide, 5 parts of modified expanded vermiculite, 10 parts of modified halloysite powder, 2 parts of dimethyl silylated silica, 10 parts of VP-dimethylaminoethyl methacrylate copolymer, 12 parts of nano aerogel, 30 parts of silicone resin, 3 parts of dispersant, 1 part of leveling agent, 1 part of defoamer, 3 parts of fumed silica and 12 parts of turpentine.

[0074] The preparation method of the modified expanded vermiculite comprises the following steps: preparing a coating modifier according to the mass ratio of ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100:5:1; passing the expanded vermiculite through a 325-mesh sieve and taking the sieve bottom; drying the sieved expanded vermiculite at 100°C for 3h, adding the dried expanded vermiculite to the coating modifier according to the ratio of expanded vermiculite: coating modifier = 1:5, stirring at 45°C for 1h to obtain coated modified expanded vermiculite, centrifuging, taking the precipitate and drying it at 90°C, breaking it up, and obtaining the modified expanded vermiculite.

[0075] In the above-mentioned coating, the preparation method of the modified halloysite powder comprises the following steps: preparing an intercalation modifier according to the mass ratio of ethanol: pentaerythritol tetracocoate = 100:3; passing the halloysite powder through a 325-mesh sieve and taking the sieve bottom; drying the sieved halloysite powder at 100°C for 3h, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder: intercalation modifier = 1:5, stirring at 45°C for 3h to obtain intercalation-modified halloysite powder, centrifuging, taking the precipitate and drying it at 90°C, breaking it up, and obtaining modified halloysite powder.

[0076] In the above coating, the particle size range of ammonium polyphosphate is below 250 mesh sieve; the particle size range of the rutile titanium dioxide is below 325 mesh sieve; the particle size range of the dimethyl silylate silica is below 200 mesh sieve.

[0077] The preparation method of the above-mentioned thermal insulation coating comprises the following steps:

[0078] The glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

[0079] S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 1000 r / min, then add dispersant and turpentine in sequence, and stir for 10 minutes; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1500 r / min, and stir for 20 minutes; obtain mixture A.

[0080] S2: Transfer mixture A to a sand mill, add 40 parts by mass of grinding media, i.e. glass beads with a diameter of 2 mm, and grind at 800 r / min for 1 hour to improve the uniformity and flatness of the coating; filter and remove the grinding media to obtain ground material B.

[0081] S3: Transfer the ground material B back to the high-speed disperser, add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a speed of 800 r / min, and stir for 15 minutes; finally, add the leveling agent and defoamer, and continue stirring for 10 minutes to obtain a uniform and stable thermal insulation coating.

[0082] In the above embodiments: the particle size range of the glass beads is 10μm to 250μm, and the wall thickness range is 1μm to 2μm; the diameter range of the ceramic fiber is 3μm to 10μm, and the length is 0.1mm to 0.5mm; the diameter range of the alumina fiber is 3μm to 10μm, and the length is 0.1mm to 0.5mm; the particle size range of the nano aerogel is below 100nm. Silica dimethyl silylate comes from Hubei Shixing Chemical Co., Ltd.; fumed silica is Wacker HDK H20BET200, which comes from Shanghai Yunhe Materials Technology Co., Ltd.; nano aerogel comes from Lingshou County Jinyuan Mining Processing Plant; VP-dimethylaminoethyl methacrylate copolymer comes from Shanghai Yuyu New Materials Technology Co., Ltd.; silicone resin is a liquid resin, Dow Corning RSN-0805 resin, which comes from Guangzhou Rongda Chemical Co., Ltd.; dispersant is sodium hexametaphosphate; leveling agent is acrylate leveling agent, model LS3022, which comes from Kunshan Loris Polymer Materials Co., Ltd.; defoamer is polyether modified silicone defoamer, model W-650, which comes from Guangzhou Weixin Innovation Materials Co., Ltd.; turpentine comes from Jinan Tiantai Chemical Co., Ltd.; dicetearyl dimer linoleate comes from Jinjinle (Hunan) Chemical Co., Ltd., PVP K30 is polyvinyl pyrrolidone K30, which comes from Shanghai Changyu Chemical New Materials Co., Ltd.; pentaerythritol tetracocoate comes from Shanghai Donghui Chemical Technology Co., Ltd.

[0083] Comparative Example 1

[0084] In the coating, the expanded vermiculite is not modified, and the modified expanded vermiculite is directly replaced by the expanded vermiculite; other parameters and methods are the same as in Example 1.

[0085] Comparative Example 2

[0086] In the coating, the halloysite powder is not modified, and the modified halloysite powder is directly replaced by the halloysite powder; other parameters and methods are the same as in Example 1.

[0087] Comparative Example 3

[0088] In the coating, the expanded vermiculite is not modified, and the modified expanded vermiculite is directly replaced by the expanded vermiculite; the halloysite powder is not modified, and the modified halloysite powder is directly replaced by the halloysite powder; other parameters and methods are the same as in Example 1.

[0089] Comparative Example 4

[0090] In the coating, no modified expanded vermiculite and modified halloysite powder are added, and the mass fractions of the modified expanded vermiculite and the modified halloysite powder are replaced by glass microspheres; other parameters and methods are the same as in Example 1.

[0091] Comparative Example 5

[0092] No silica dimethyl silylate was added to the coating; other parameters and methods were the same as in Example 1.

[0093] Comparative Example 6

[0094] No VP-dimethylaminoethyl methacrylate copolymer was added to the coating; other parameters and methods were the same as in Example 1.

[0095] Comparative Example 7

[0096] In the coating, the expanded vermiculite is not modified, and the modified expanded vermiculite is directly replaced by the expanded vermiculite; the halloysite powder is not modified, and the modified halloysite powder is directly replaced by the halloysite powder; no silica dimethyl silylate is added; no VP-dimethylaminoethyl methacrylate copolymer is added; other parameters and methods are the same as in Example 1.

[0097] Comparative Example 8

[0098] In the preparation method, S2 is omitted and no sand mill is used for grinding; other parameters and methods are the same as in Example 1.

[0099] The coatings prepared in the above-mentioned embodiments and comparative examples were tested for their performance.

[0100] 1. Sample:

[0101] Substrate: 4 mm thick low carbon steel plate, the thermal conductivity of the bare steel plate is 45 W / (m·K), the steel plate is sandblasted, and then the coatings of the embodiments and comparative examples are respectively applied by scraping, and the coating thickness is 1 mm.

[0102] 2. Project testing:

[0103] (1) Adhesion test: The test was conducted according to GB / T 9286 "Scratching test for paint and varnish films". A 10×10 grid of 2 mm×2 mm was drawn on the surface of the sample using a scribing knife. After scribing, adhesive tape was tightly attached to the small grid to be tested, and the tape was rubbed hard with an eraser, and then quickly torn off in a vertical direction. The adhesion was graded according to the degree of coating shedding. The test results are shown in Table 1 below.

[0104] (2) Water resistance test: According to GB / T 1733 "Determination of water resistance of paint film", the test sample is placed in distilled water, immersing 2 / 3 of the length of the test plate in water, and the water temperature is adjusted to 25°C. After 240 hours, observe whether the test plate has loss of gloss, discoloration, blistering, wrinkling, shedding, rust, etc. The test results are shown in Table 1 below.

[0105] Water resistance evaluation level: Level 1: The coating is intact and remains in its original state, with no gloss loss, color change, blistering, wrinkling, peeling, rust, etc.; Level 2: The coating surface has slight changes, such as a lighter degree of gloss loss and slightly lighter color, but it does not affect the overall performance of the coating; Level 3: The coating surface has obvious changes, such as a heavier degree of gloss loss, color change, blistering, wrinkling, peeling, rust, etc., but it has not reached the level of serious damage; Unqualified: The coating has serious bubbles, shedding, rust, etc., and the water resistance is poor and cannot meet the use requirements.

[0106] (3) Thermal conductivity test: The test was conducted according to GB / T 10295 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Heat Flow Meter Method", using WPY heat flow meter thermal conductivity tester DX-8377, with the hot surface temperature controlled at 70°C and the cold surface temperature controlled at room temperature. The device was turned on and the thermal conductivity of the sample was automatically tested using a computer. The test results are shown in Table 1 below.

[0107] (4) Combustion growth rate index test: The test was conducted using a FTT0007 cone calorimeter. A 3 mm thick thermal insulation coating was filled into the sample box, and the sides and bottom were wrapped with tin foil. The test was conducted after the radiation cone was preheated to determine the combustion growth rate index of the coating. The test results are shown in Table 1 below.

[0108] (5) Salt spray resistance test: According to the test method of GB / T 1771 "Determination of neutral salt spray resistance of paints and varnishes", the coated sample is placed on the sample rack of the salt spray test chamber and subjected to a neutral salt spray test (sodium chloride solution concentration of 5%, test temperature of 35°C, salt spray deposition rate of 1.2ml / 80cm 2 / h), and after the spraying lasted for 500h, the state of the coating surface was observed. The test results are shown in Table 1 below.

[0109] Salt spray resistance evaluation level, level 10: no defective area of ​​the coating, no change in the appearance of the sample surface; level 9: the coating defect area accounts for less than 0.1%, and the sample surface has slight to moderate discoloration; level 8: the coating defect area accounts for greater than or equal to 0.1% and less than 0.25%, and the sample surface is severely discolored or has very slight corrosion products; level 7: the coating defect area accounts for greater than or equal to 0.25% and less than 0.5%, and the sample surface is severely glossy or has very slight corrosion products; level 6: the coating defect area accounts for greater than or equal to 0.5% and less than 1.0%, and the sample surface is severely glossy or there is a thin layer of corrosion products or pitting on the local surface of the sample; level 5: the coating defect area accounts for greater than or equal to 1 .0%, less than 2.5%, there are corrosion products or pitting on the surface of the sample, and one of them is distributed on the entire surface of the sample; Level 4: The coating defect area accounts for greater than or equal to 2.5% and less than 5%, and there is a thick corrosion product layer or pitting on the surface of the sample; Level 3: The coating defect area accounts for greater than or equal to 5% and less than 10%, and there is a very thick corrosion product layer or pitting on the surface of the sample, and there are deep pitting; Level 2: The coating defect area accounts for greater than or equal to 10% and less than 25%, and the sample has the phenomenon of base metal corrosion; Level 1: The coating defect area accounts for greater than or equal to 25% and less than 50%, which is a serious corrosion phenomenon; Level 0: The coating defect area accounts for more than 50%, which is a very serious corrosion phenomenon.

[0110] (6) According to GB / T 1865 “Artificial weathering and artificial radiation exposure of paints and varnishes to filtered xenon arc radiation”, the xenon lamp accelerated weathering test was carried out with a light intensity of 0.65 W / m 2 ·nm; when the light is strong during the day, the temperature is set to 60℃ and the humidity is 40% to simulate the high temperature environment under direct sunlight; at night (when the light stops), the temperature is reduced to 30℃ and the humidity is 60% to form a temperature difference between day and night; spray once every 6 hours, and each spray time is 15 minutes; the hardness of the spray water is controlled at 80mg / L (calculated as calcium carbonate), and 0.2% sodium chloride is added to the spray water to adjust the pH to 5.0. The test time is 1200 hours. After the test, the water resistance, thermal conductivity and combustion growth rate index of the coating are measured. The test results are shown in Table 1 below.

[0111] Table 1 Coating performance test results

[0112]

[0113] It can be seen from the above experimental results that the thermal insulation coatings prepared in Examples 1 to 5 have good thermal insulation properties, can block heat conduction, and play a role in thermal insulation. At the same time, they also have excellent weather resistance, are waterproof, fireproof, and corrosion-resistant, and can maintain good performance under complex and changeable climatic conditions. It can be seen from the results of Comparative Example 1 that after the expanded vermiculite is modified, the coated modifier on the surface can improve the compatibility of the expanded vermiculite with other components in the coating, so that it is more evenly dispersed in the coating system, thereby achieving better thermal insulation, fire prevention, corrosion resistance and weather resistance effects; It can be seen from the results of Comparative Example 2 that after the halloysite powder is modified, the surface properties are improved, and the interaction with other components in the coating is enhanced, thereby achieving better thermal insulation, fire prevention, corrosion resistance and weather resistance effects; It can be seen from the results of Comparative Example 3 that the expanded vermiculite and halloysite powder are not modified, and the thermal insulation, fire prevention, corrosion resistance and weather resistance of the coating are all reduced; It can be seen from the results of Comparative Example 4 that the modified expanded vermiculite and modified halloysite powder are not added to the coating, which affects the thermal insulation performance of the coating, and at the same time, the waterproof, fire prevention, corrosion resistance and weather resistance of the coating are also weakened accordingly; From the results of Example 5, it can be seen that silica dimethyl silylate can form a hydrophobic siloxane network structure on the surface of the coating to prevent the intrusion of moisture and harmful gases, thereby improving the water resistance, weather resistance and other properties of the coating; from the results of Comparative Example 6, it can be seen that VP-dimethylaminoethyl methacrylate copolymer can form a protective film on the surface of the coating and improve the compatibility of each component, thereby improving the various properties of the coating; from the results of Comparative Example 7, it can be seen that the expanded vermiculite and halloysite powder in the coating are not modified, and at the same time, silica dimethyl silylate and VP-dimethylaminoethyl methacrylate copolymer are not added, and the thermal insulation, fire prevention, corrosion resistance and weather resistance functions of the coating are significantly weakened; from the results of Comparative Example 8, it can be seen that the grinding step of mixture A is removed in the preparation method, the uniformity of the coating is deteriorated, and the thermal insulation, fire prevention, corrosion resistance and weather resistance functions are weakened.

Claims

1. A thermal insulation coating, characterized in that: The coating includes the following raw materials in parts by mass: 25 to 35 parts of glass microbeads, 12 to 20 parts of ceramic fibers, 4 to 8 parts of alumina fibers, 4 to 7 parts of ammonium polyphosphate, 3 to 6 parts of rutile titanium dioxide, 5 to 8 parts of modified expanded vermiculite, 5 to 10 parts of modified halloysite powder, 2 to 5 parts of dimethyl silylate silica, 6 to 10 parts of VP-dimethylaminoethyl methacrylate copolymer, 12 to 18 parts of nano aerogel, 20 to 30 parts of silicone resin, 3 to 4 parts of dispersant, 0.5 to 1 part of leveling agent, 1 to 3 parts of defoaming agent, 1 to 3 parts of fumed silica and 10 to 15 parts of turpentine.

2. A thermal insulation coating according to claim 1, characterized in that: The preparation method of the modified expanded vermiculite comprises the following steps: drying the expanded vermiculite at a temperature of 100 to 120° C. for 2 to 3 hours, adding the dried expanded vermiculite to the coating modifier at a ratio of expanded vermiculite to coating modifier = 1: (5 to 8), stirring at a temperature of 35 to 45° C. for 1 to 2 hours to obtain coated modified expanded vermiculite, centrifugally separating, taking the precipitate and drying it at 80 to 90° C., breaking it up, and obtaining the modified expanded vermiculite.

3. A thermal insulation coating according to claim 2, characterized in that: The particle size range of the expanded vermiculite is 250-325 mesh sieve; the mass ratio of the components of the coating modifier is ethanol: dicetyl stearyl dimer linoleate: PVP K30 = 100: (2-5): (1-3).

4. The thermal insulation coating according to claim 1, characterized in that: The preparation method of the modified halloysite powder comprises the following steps: drying the halloysite powder at 100° C. to 120° C. for 2 h to 3 h, adding the dried halloysite powder to the intercalation modifier according to the ratio of halloysite powder to intercalation modifier = 1: (5 to 8), stirring at 35° C. to 45° C. for 3 h to 5 h to obtain intercalation-modified halloysite powder, centrifuging, drying the precipitate at 80° C. to 90° C., breaking it up, and obtaining the modified halloysite powder.

5. A thermal insulation coating according to claim 4, characterized in that: The particle size range of the halloysite powder is 250-325 mesh sieve; the mass ratio of the intercalation modifier is ethanol: pentaerythritol tetracocoate = 100: (3-8).

6. The thermal insulation coating according to claim 1, characterized in that: The particle size of the glass microspheres ranges from 10 μm to 250 μm, and the wall thickness ranges from 1 μm to 2 μm; the diameter of the ceramic fibers ranges from 3 μm to 10 μm, and the length ranges from 0.1 mm to 0.5 mm; the diameter of the alumina fibers ranges from 3 μm to 10 μm, and the length ranges from 0.1 mm to 0.5 mm.

7. The thermal insulation coating according to claim 1, characterized in that: The particle size range of the ammonium polyphosphate is through a 250-325 mesh sieve; the particle size range of the rutile titanium dioxide is through a 250-325 mesh sieve; the particle size range of the dimethyl silylate silica is through a 200-250 mesh sieve; and the particle size range of the nano aerogel is below 100 nm.

8. A method for preparing a thermal insulation coating, used for preparing the thermal insulation coating according to claim 1, characterized in that: The preparation method comprises the following steps: S1: Add silicone resin into a high-speed disperser according to the mass fraction, set the speed to 800r / min-1000r / min, then add dispersant and turpentine in sequence, and stir for 10min-15min; then add glass microbeads, ceramic fiber, alumina fiber, modified expanded vermiculite, and modified halloysite powder in sequence, increase the speed to 1200r / min-1500r / min, and stir for 20min-30min; obtain mixture A; S2: Transfer the mixture A to a sand mill, add grinding media, and grind at 500 r / min to 800 r / min for 1 h to 2 h to improve the uniformity and flatness of the coating; Filter and remove the grinding medium to obtain grinding material B; S3: Transfer the ground material B back to the high-speed disperser, add ammonium polyphosphate, rutile titanium dioxide, dimethyl silylated silica, VP-dimethylaminoethyl methacrylate copolymer, nano aerogel, and fumed silica in sequence at a rotation speed of 600r / min to 800r / min, and stir for 15min to 25min; finally, add the leveling agent and defoamer, and continue stirring for 5min to 10min to obtain a uniform and stable thermal insulation coating.

9. The method for preparing a heat insulating coating according to claim 8, characterized in that: In S2, the grinding media are glass beads with a diameter of 2 mm to 3 mm; the grinding media are added in an amount of 30 to 40 parts by mass.

10. The method for preparing a heat insulating coating according to claim 8, characterized in that: The glass microspheres, ceramic fibers, alumina fibers, modified expanded vermiculite and modified halloysite powder are dried separately to remove moisture before being mixed.

Citation Information

Patent Citations

  • Novel nano ceramic thermal insulation material

    CN106366860A

  • Heat insulation coating

    CN107936823A

  • Wear-resistant, cleaning-resistant and mark-free teaching blackboard coating and preparation method thereof

    CN118685112A

  • Enamel veneering repair material and preparation method thereof

    CN119139140A

  • Anti-corrosive agents and method for protecting metal surfaces against corrosion

    CN1398306A